Analisis Penggunaan Asuransi Jiwa dalam Pembiayaan Mudharabah di BPRS Gebu Prima Medan - Ryan Hidayat; Maryam Batubara (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This research discusses the use of life insurance in mudharabah financing at BPRS Gebu Prima Medan. The introduction explains the background to the importance of using life insurance in the context of sharia financing, especially in minimizing credit risk and providing financial protection for customers. The literature review outlines theories related to sharia financing and the role of life insurance in risk management. The research method used is a qualitative approach with data collection techniques in the form of interviews and direct observation. The research results show that the majority of BPRS Gebu Prima Medan customers who take advantage of mudharabah financing also take out life insurance protection. The profile of customers who tend to use life insurance are those who have a significant risk of death, such as micro and small entrepreneurs with large family responsibilities. However, there is still a small number of customers who have not utilized life insurance products, so further research is needed to understand the factors that influence customer decisions and strategies that can be implemented to increase the adoption of life insurance products among customers.